The Novel Oral Anticoagulants for Acute Venous Thromboembolism: Is Warfarin Dead? - Cohen, Alexander T.; Granziera, Serena; Veronese, Nicola; Zoppellaro, Giacomo (Seminars in Respiratory and Critical Care Medicine, 2017)
The direct oral anticoagulants (DOACs) have been compared with parenteral anticoagulants and vitamin K antagonists (VKAs) for the treatment of venous thromboembolism (VTE) in several robust studies. DOACs have shown similar efficacy in preventing recurrent VTE and significant reductions in critical site (intracranial) bleeding, fatal bleeding, major and nonmajor bleeding. Warfarin and other VKAs are not dead as treatment modalities for VTE. A better way to describe the current situation is to use a boxing expression, “down but not out.” VKAs and parenteral anticoagulants still have a role to play in the management of VTE in several clinical settings. In indications where DOACs can be used, VKAs should not, as the safety profile of VKAs is considerably worse than DOACs. Hence, guidelines are now recommending DOACs in preference to VKAs. In this article, we consider where DOACs are indicated, where there is growing evidence for use, where we have little evidence for use, and finally where there is no evidence for use and where they, thus, should not be used. We have included recommendations and examples of our own practice which may not be applicable to all settings.
Keywords: venous thromboembolism; oral anticoagulation; warfarin; non-VKA oral anticoagulants; safety; efficacy